Excess Cerebrovascular Mortality in the United States During the COVID-19 Pandemic. Issue 2 (February 2021) - Sharma, Richa; Kuohn, Lindsey R.; Weinberger, Daniel M.; Warren, Joshua L.; Sansing, Lauren H.; Jasne, Adam; Falcone, Guido; Dhand, Amar; Sheth, Kevin N.
Abstract : Background and Purpose: The magnitude and drivers of excess cerebrovascular-specific mortality during the coronavirus disease 2019 (COVID-19) pandemic are unknown. We aim to quantify excess stroke-related deaths and characterize its association with social distancing behavior and COVID-19–related vascular pathology. Methods: United States and state-level excess cerebrovascular deaths from January to May 2020 were quantified using National Center for Health Statistic data and Poisson regression models. Excess cerebrovascular deaths were analyzed as a function of time-varying stroke-related emergency medical service (EMS) calls and cumulative COVID-19 deaths using linear regression. A state-level regression analysis was performed to determine the association between excess cerebrovascular deaths and time spent in residences, measured by Google Community Mobility Reports, during the height of the pandemic after the first COVID-19 death (February 29). Results: Forty states and New York City were included. Excess cerebrovascular mortality occurred nationally from the weeks ending March 28 to May 2, 2020, up to a 7.8% increase above expected levels during the week of April 18. Decreased stroke-related EMS calls were associated with excess stroke deaths one (70 deaths per 1000 fewer EMS calls [95% CI, 20–118]) and 2 weeks (85 deaths per 1000 fewer EMS calls [95% CI, 37–133]) later. Twenty-three states and New York City experienced excess cerebrovascular mortality during the pandemic height. A 10% increase in time spent at home was associated with a 4.3% increase in stroke deaths (incidence rate ratio, 1.043 [95% CI, 1.001–1.085]) after adjusting for COVID-19 deaths. Conclusions: Excess US cerebrovascular deaths during the COVID-19 pandemic were observed and associated with decreases in stroke-related EMS calls nationally and mobility at the state level. Public health measures are needed to identify and counter the reticence to seeking medical care for acute stroke during the COVID-19 pandemic. Abstract : Supplemental Digital Content is available in the text.